VD_FINDINFO HC / 2013 / 355 vom 30. April 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, LOCAL PROFESSIONNEL, RÉSILIATION, ANNULABILITÉ | 253a al. 1 CO, 271 al. 1 CO, 271a al. 1 let. e CO, 271a al. 3 let. a CO